Electromagnetic Regulation of Cell Activity - Stanley, Sarah A. (Cold Spring Harb Perspect Med, 2019)
The ability to observe the effects of rapidly and reversibly regulating cell activity in targeted cell populations has provided numerous physiologic insights. Over the last decade, a wide range of technologies have emerged for regulating cellular activity using optical, chemical, and, more recently, electromagnetic modalities. Electromagnetic fields can freely penetrate cells and tissue and their energy can be absorbed by metal particles. When released, the absorbed energy can in turn gate endogenous or engineered receptors and ion channels to regulate cell activity. In this manner, electromagnetic fields acting on external nanoparticles have been used to exert mechanical forces on cell membranes and organelles to generate heat and interact with thermally activated proteins or to induce receptor aggregation and intracellular signaling. More recently, technologies using genetically encoded nanoparticles composed of the iron storage protein, ferritin, have been used for targeted, temporal control of cell activity in vitro and in vivo. These tools provide a means for noninvasively modulating gene expression, intracellular organelles, such as endosomes, and whole-cell activity both in vitro and in freely moving animals. The use of magnetic fields interacting with external or genetically encoded nanoparticles thus provides a rapid noninvasive means for regulating cell activity.